Creating Age-Friendly City Through Inclusive Public Space Design - Danang Febriyantoko; Muhammad Fikri Hanafi (TUMATA: Journal of Arts and Cultural Management, 2025)
Indonesia will become one of the countries experiencing demographic aging, and the percentage of people over 65 years old will continue to increase every year. Yogyakarta is known as a province with a higher elderly population than the national average. The Yogyakarta City Government has an integrated service program for the elderly at the sub-district level to create an elderly-friendly city. This study aims to provide design innovation through an inclusive design approach by analyzing the spatial pattern of elderly-friendly villages. This study will take a case study of the implementation of the Integrated Elderly Service program in Wirogunan sub-district as a pilot project, specifically in Bintaran village. From the results of this study, several recommendations can be put forward, one of which is the need for a green open space management program in the Bintaran village environment. This can be a more environmentally friendly solution by involving all elements of society, from young to old, working together to create elderly-friendly public facilities.